Effects of processing on the chemical composition of rice - Arslan, S.; Erbas, M.; Candal, C.; Mutlu, C. (Wageningen Academic Publishers, 2016)
Changes in the chemical composition of rice from harvest to packaging were searched. The phytic acid content in rice bran and final white rice was 64.25 and 9.66 mg/g (dry basis; db), respectively. Sugars (fructose, glucose, and sucrose), organic acids (citric and malic), and free amino acids (alanine, aspartic, and glutamic acid) decreased according to the progressing stages. The most abundant phenolic compound present in rice kernels was ferulic acid. The antioxidant capacity of rice bran was 428.97 mu M Trolox equivalent (TE)/g (db), and it dropped from 126.23 to 60.76 mu M TE/g (db) during processing. The L* colour value of rice samples showed a linear increase with decreasing antioxidant capacity. About half the phytic acid content and antioxidant activity was removed as a consequence of the dehulling, whitening, polishing, and grading of rice kernels.
Keywords: ferulic acid; paddy rice; process; TEAC